Gut microbiota-derived imidazole propionate predicts cardiometabolic risk in patients with coronary artery disease - Wenzl, Florian A.; Wang, Peizhi; Kahles, Florian; Beck, Katharina R; Giannitsis, Evangelos; Obeid, Slayman; Bruno, Francesco; Li, Xinmin S; Nanchen, David; Liberale, Luca; Smolle, Maria A; Schweiger, Victor; et al. (European heart journal, 2025)
The gut microbiota is a modulator of cardiometabolic disease. Circulating imidazole propionate (ImP) is a microbiota-derived proatherogenic amino acid metabolite modulating the inflammatory response of myeloid cells, endothelial function, and glucose metabolism. This study examined the prognostic value of ImP in patients with coronary artery disease (CAD).Circulating ImP levels were measured in independent prospective cohorts of patients with acute coronary syndrome (ACS; Swiss ACS cohort n = 4787, Swiss cardiac magnetic resonance imaging cohort n = 150, German ACS cohort n = 1428) and chronic coronary syndrome (CCS; German CCS cohort n = 701). Major adverse cardiovascular events (MACE), defined as the first occurrence of a composite of death, non-fatal myocardial infarction, or non-fatal stroke after admission, were the primary endpoint. Cox models, accounting for established risk factors including the gut-derived cardiovascular risk factor trimethylamine N-oxide, were used to evaluate the predictive value of ImP.Circulating ImP was associated with more advanced CAD and with cardiometabolic characteristics including diabetes and elevated high-sensitivity C-reactive protein. High ImP was an independent predictor of MACE [Swiss ACS cohort: hazard ratio (HR) per log2 increase 1.22, 95% confidence interval (CI) 1.10-1.35, P < .001; German ACS cohort: HR 2.34, 95% CI 1.46-3.76, P < .001; German CCS cohort: HR 1.32, 95% CI 1.13-1.53, P < .001)] and of mortality (Swiss ACS cohort: HR 1.34, 95% CI 1.17-1.54, P < .001; German ACS cohort: HR 2.38, 95% CI 1.48-3.82, P < .001; German CCS cohort: HR 1.50, 95% CI 1.14-1.98, P = .004) after adjustment for established risk factors. Imidazole propionate provided predictive value beyond trimethylamine N-oxide (Swiss ACS cohort: HR 1.30, 95% CI 1.05-1.61, P = .014; German CCS cohort: HR 1.31, 95% CI 1.12-1.53, P = .001).Gut microbiota-derived ImP predicted MACE in patients with CAD independently of traditional risk factors and holds promise as a therapeutic target. Imidazole propionate may refine risk stratification for personalized secondary prevention strategies.